ChemInform Abstract: One‐Pot Synthesis of Bis(amino)‐1, 2, 4‐thiadiazoles via Direct SNAr. Issue 22 (13th May 2013) - Beeley, Howard A.; Degorce, Sebastien; Harris, Craig S.; Lecoq, Jonathan; Morgentin, Remy; Perkins, David
Abstract The selective SNAr reaction of dichloro‐1, 2, 4‐thiadiazole with amines at the 5‐position can be easily combined with a second SNAr reaction to produce unsymmetrically disubstituted 3, 5‐bis(amino)‐1, 2, 4‐thiadiazole libraries.